Friedrich Schiller on the Role of Beauty in Social Life - Sasnauskienė, Jadvyga (Problemos, 1980)
The article focuses on the aesthetic views of Friedrich Schiller. In search of an alternative to the spiritual crisis of the capitalist society, Schiller arrived at a conclusion that aesthetic education is the basic means of the preservation of the individuality of man, because he thought only beauty to have overall influence on the individuality of man by way of developing his multifarious interests and creative capacity. The author of the present article points out that, irrespective of the utopian character of his views, Friedrich Schiller contemplated a number of feasible concepts pertaining to the analysis of the specific influence of beauty on individuality.